(untitled) (Architecture Image Studies, 2025)
In the context of rapid urbanization and cultural integration, park sculpture has become an essential component in shaping urban aesthetics, enriching public cultural spaces, and enhancing the spiritual life of city dwellers. As Vietnam’s largest economic, cultural, and scientific center, Ho Chi Minh City holds significant potential for the development of park sculpture systems that harmoniously connect art, public spaces, and local cultural identity. However, field surveys reveal that the number of sculptures in public parks remains limited, their distribution uneven, and in many cases, public parks lack artistic works altogether. Furthermore, the artistic quality of some sculptures is inconsistent, often failing to integrate with surrounding landscapes or to meet the aesthetic needs of the community. This article examines the current situation of park sculpture in cultural spaces across Ho Chi Minh City, identifying key limitations in planning, management, investment, and preservation. Based on these findings, it proposes practical solutions, including: developing long-term strategies for integrating park sculpture into sustainable urban planning; strengthening collaboration among authorities, artists, and communities; encouraging socialization and diversifying investment resources; and enhancing conservation and restoration of existing works. Implementing these solutions not only elevates the aesthetic and cultural value of public spaces in Ho Chi Minh City but also contributes to building an image of a modern, humane, and culturally rich metropolis.